We are in a book! - Willems, Mo. (New York : Hyperion Books for Children, 2010)
Piggie realizes that she and Gerald the elephant are in a book and that she can make the reader say words, but when Gerald comes to understand the danger of the book ending, Piggie comes up with a solution to get the reader to keep reading.
Booklist
Kirkus Starred
School Library Journal starred
Booklist, September 2010
Bulletin (Center for Children's books), October 2010
Kirkus Starred, September 2010
Keywords: Books and reading -- Juvenile fiction; Elephants -- Juvenile fiction; Swine -- Juvenile fiction; Books and reading -- Fiction; Elephants -- Fiction; Humorous stories; Pigs -- Fiction; Books and reading -- Fiction; Elephants -- Fiction; Humorous fiction; Pigs -- Fiction; Humorous fiction; Readers (Elementary).